Uçucu Külün Karbon Fiber Takviyeli Hafif Betonun Seebeck Katsayısına Etkisi - Demirel, Bahar; Yazıcıoğlu, Salih (Sedat ÇETİN, 2007)
Karbon fiber takviyeli beton, sahip olduğu Seebeck etkisinden dolayı, sıcaklığı sezebilen kompozit bir malzemedir. Kompozite bu yeteneği veren içerisindeki iletken karbon fiberlerdir. Karbon fiber takviyeli hafif betonun sıcaklığı sezebilme kabiliyeti ve mineral katkının Seebeck etkisi üzerindeki tesiri bu çalışmada incelenmiştir. Ayrıca Bu amaçla, uçucu kül, CEM I 42,5 portland çimento, pomza agregası ve karbon fiber kullanılarak hazırlanan toplam 4 tip serinin termoelektrik ölçümleri hazırlanan deney düzeneği ile gerçekleştirilmiştir. Sonuçta, karbon fiber takviyeli hafif betonun da karbon fiber takviyeli normal beton gibi Seebeck etkisine sahip olduğu fakat uçucu külün malzemenin Seebeck katsayısını düşürdüğü görülmüştür.

Carbon fiber reinforced concrete is a composite material which can sense temperature due to the Seebeck Effect. This sensing ability is given to the composite by the conductive short carbon fibers. In this study, both the temperature sensing ability of the carbon fiber reinforced lightweight concrete and the influence of the mineral admixture on the Seebeck Effect have been investigated. With this aim, the thermoelectrical measurements of four series of samples which were produced with fly ash, CEM I 42,5 Portland cement, pumice aggregate and carbon fiber performed with the experimental setup. Consequently, it was seen that carbon fiber reinforced lightweight concrete also has got Seebeck Effect like the carbon fiber reinforced normal concrete but fly ash was decreased the Seebeck coefficient of the material.
The Effect of the Fly Ash on the Seebeck Coefficient of the Carbon Fiber Reinforced Lightweight Concrete